Pemberdayaan Guru dalam Penggunaan Media Digital untuk Pembelajaran Sastra di SMPN 2 Makassar - Anita Candra Dewi; Sutarsi Suhaeb; Mantasia Mantasia; Saharuddin Saharuddin; Ninik Rahayu Ashadi (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of digital media in education is increasingly important to support a more interactive and interesting learning process, including in literature learning. This article discusses a community service program that aims to empower teachers in schools to utilize digital media as a means for more effective and enjoyable literature learning. Through training and workshops, teachers are given an understanding and skills in using various digital platforms, such as videos, learning applications, and e-books, to increase students' interest in reading and appreciation of literature. The results of this activity show an increase in teachers' skills in integrating digital media in literature learning as well as an increase in students' enthusiasm in learning literature. Thus, teacher empowerment through the use of digital media is expected to optimize the literature learning process in schools, as well as answer the challenges of education in the digital era.